Neuroimaging predictors of structural epilepsy in the COVID-19 catamnesis - N. E. Maslov; N. V. Yuryeva; E. I. Khamtsova; A. A. Litvinova (Эпилепсия и пароксизмальные состояния)
Respiratory system pathology is the most common clinical disorder associated with COVID-19. However, there are also lesions of the immune, cardiovascular, genitourinary, endocrine systems, and digestive tract. In addition, there are numerous reports on infection-related neurological manifestations, which can be divided into 3 groups: central nervous system manifestations (headache and dizziness, stroke, encephalopathy, encephalitis, acute myelitis), lesions of the peripheral nervous system (anosmia, Guillain–Barre syndrome), secondary lesions in the skeletal muscles. Brain damage that occurs during novel coronavirus infection and determines some of the above-mentioned manifestations often account for the development of structural epilepsies. Only a few scarce review articles on neuroimaging features in patients with COVID-19 have been found in Russian research publications.The objective of the review was to collect, analyze and summarize the results of brain magnetic resonance imaging (MRI), currently accumulated worldwide in patients with COVID-19. We present the most common diagnoses based on brain MRI in patients with COVID-19 established by foreign researchers from March 2020 to March 2021, as well as initial attempts to interpret the pathophysiological mechanisms of the changes observed in the brain substance.